Yellowing of a red south african kandiudult, studied by means of mössbauer spectroscopy - Van Ranst, E. (Lippincott Williams and Wilkins, 2016)
An Acrudoxic Kandiudult soil profile from Farmhill, KwaZulu-Natal Province, South Africa, was analyzed by Mössbauer spectroscopy as an example of a red soil with yellowish surface horizons, a common sequence for which iron oxide characteristics are only poorly documented. In the red lower part of the profile (62+ cm), the Fe oxide fraction consists of hematite and well-crystallized pure goethite. In the yellowish upper part (0-62 cm), the relative hematite content is lower, goethite shows a high degree of Al-for-Fe substitution, and ferrihydrite is present. Processes found to have affected the Fe oxide fraction are hematite dissolution, partial leaching, goethite precipitation with a high degree of Al incorporation, and ferrihydrite formation in conditions with a high organic matter content; the so-called DOM (dissolved organic matter) ferrihydrites. © 2016 Wolters Kluwer Health, Inc.